2016
DOI: 10.1016/j.chom.2016.04.004
|View full text |Cite
|
Sign up to set email alerts
|

A Burkholderia Type VI Effector Deamidates Rho GTPases to Activate the Pyrin Inflammasome and Trigger Inflammation

Abstract: Burkholderia cenocepacia is an opportunistic pathogen of the cystic fibrosis lung that elicits a strong inflammatory response. B. cenocepacia employs a type VI secretion system (T6SS) to survive in macrophages by disarming Rho-type GTPases, causing actin cytoskeletal defects. Here, we identified TecA, a non-VgrG T6SS effector responsible for actin disruption. TecA and other bacterial homologs bear a cysteine protease-like catalytic triad, which inactivates Rho GTPases by deamidating a conserved asparagine in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
149
1
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 151 publications
(160 citation statements)
references
References 63 publications
9
149
1
1
Order By: Relevance
“…Because the PYRIN inflammasome also plays a role in the detection of B. cenocepacia in human and mouse macrophages [20,31,32], we next compared B. cenocepacia -induced CASP4 expression and the activation of CASP1 in WT, mefv −/- , and casp4 −/- macrophages at 6 h post infection via immunoblot. Expression of CASP4 in response to B. cenocepacia was markedly induced in WT and mefv −/- macrophages (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Because the PYRIN inflammasome also plays a role in the detection of B. cenocepacia in human and mouse macrophages [20,31,32], we next compared B. cenocepacia -induced CASP4 expression and the activation of CASP1 in WT, mefv −/- , and casp4 −/- macrophages at 6 h post infection via immunoblot. Expression of CASP4 in response to B. cenocepacia was markedly induced in WT and mefv −/- macrophages (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The T6SS of B. cenocepacia is essential for intracellular pathogenicity [19,32]. Accordingly, T6SS deficiency led to enhanced phagocytosis and the impairment of bacterial replication in WT macrophages (Fig S4B and C).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A well-established function of the T6SSs is to compete against rival bacteria in polymicrobial environments by delivering "antibacterial" toxins such as cell-wall-degrading enzymes, nucleases, and membrane-targeting enzymes, into target competitor bacterial cells (24)(25)(26)(27). Moreover, some T6SSs associated with pathogens have been reported to be involved in bacterial pathogenesis by translocating "antieukaryotic" effectors into eukaryotic cells to modulate host immunity and inflammation (28)(29)(30)(31). The well-characterized antieukaryotic effectors are several "evolved" VgrG proteins and non-VgrG phospholipases and deamidases (28)(29)(30)(31).…”
mentioning
confidence: 99%
“…Moreover, some T6SSs associated with pathogens have been reported to be involved in bacterial pathogenesis by translocating "antieukaryotic" effectors into eukaryotic cells to modulate host immunity and inflammation (28)(29)(30)(31). The well-characterized antieukaryotic effectors are several "evolved" VgrG proteins and non-VgrG phospholipases and deamidases (28)(29)(30)(31). Recently, we reported that the T6SS-4 from Yersinia pseudotuberculosis was involved in zinc transport via secretion of the zincchelating effector YezP into medium (32).…”
mentioning
confidence: 99%